Assessing campus diversity initiatives a guide for campus practitioners - Garcia, Mildred; Nettles, Michael T.; Sedlacek, William E.; Smith, Daryl G. (Understanding the difference diversity makes, 2001)
This volume, one in a series of three monographs, is a guidebook to evaluating campus diversity initiatives. Chapter 1 introduces campus diversity initiatives. Chapter 2, "Evaluation and Diversity," explores the need for assessment of such initiatives. Chapter 3, "Designing a Campus Diversity Evaluation," presents general concepts and guidelines and identifies various foci of diversity assessment. It also raises questions evaluators should consider as they plan assessments and discusses data collection and analysis. Chapter 4, "Frameworks for Evaluation," offers some larger frameworks for evaluation and discusses performance indicators linked to campus diversity work. Seven appendixes contain instruments for use in evaluating campus diversity programs and student experiences. (Contains 24 references.) (SLD).